A Bibliometric Analysis of Talent Acquisition in Human Resource Management - Loso Judijanto; Rival Pahrijal; Rani Eka Arini (Westscience Press, 2026)
Talent acquisition has become a strategic pillar of human resource management (HRM) as organizations compete for scarce skills in an increasingly digitalized labor market. This study conducts a bibliometric analysis to investigate the intellectual structure, thematic evolution, influential publications, and collaboration patterns of talent acquisition research within the human resource management literature. The data were collected from the Scopus database using the keywords